Why “Good” Firms do Bad Things: The Effects of High Aspirations, High Expectations, and Prominence on the Incidence of Corporate Illegality - Mishina, Yuri; Dykes, Bernadine J.; Block, Emily S.; Pollock, Timothy G. (Academy of Management Journal, 2010)
Recent high-profile corporate scandals involving prominent, high-performing firms cast doubt on assertions that the costs of getting caught decrease the likelihood such high performers will act illegally. We explain this paradox by using theories of loss aversion and hubris to examine a sample of S&P 500 manufacturers. Results demonstrate that both performance above internal aspirations and performance above external expectations increase the likelihood of illegal activities. The sample firms' prominence enhanced the effects of performance above expectations on the likelihood of illegal actions. Prominent and less prominent firms displayed different patterns of behavior when their performance failed to meet aspirations.